The Oxford anthology of modern Indian poetry - Dharwadker, Vinay 1954-.; Ramanujan, A. K. 1929-. (Delhi Oxford University Press, 1996)
Chiefly English translation from fourteen Indian languages.
Keywords: Indic poetry -- Translations into English. -- 20th century